Green Hospital Dan Competitive Advantage Dalam Meningkatkan Kinerja Keuangan Rumah Sakit Universitas Mataram - Sahsandira; Marsya Zanira; Hadyna Aulia; Syahrul Ikhsan; Bambang (Jurnal Riset Mahasiswa Akuntansi, 2026)
This study aims to analyze the effect of Green Hospital and Competitive Advantage on the Financial Performance of Universitas Mataram Hospital. This research employed a quantitative associative approach using secondary data obtained from financial reports, operational reports, and supporting documents of Universitas Mataram Hospital from January 2023 to December 2025, resulting in 36 monthly observations. Data were analyzed using multiple linear regression with the assistance of JASP Statistics. The findings indicate that Green Hospital has a positive and significant effect on financial performance, suggesting that the implementation of environmentally sustainable practices contributes to operational efficiency and financial improvement. Conversely, Competitive Advantage, measured through the hospitalÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¢ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¾Ãƒâ€šÃ‚Â¢s digital reputation based on Google Review ratings, does not have a significant effect on financial performance. These results support the Resource-Based View Theory and Stakeholder Theory, which emphasize the importance of strategic internal resources and stakeholder-oriented sustainability practices in improving organizational performance. The study concludes that the successful implementation of Green Hospital practices can strengthen the financial sustainability of hospitals, while competitive advantage based solely on digital reputation is insufficient to directly improve financial performance.